Retoryka pamięci (z problemów mnemologii Vincenza) - Michał Kaczmarek (Przestrzenie Teorii, 2007)
This article focuses on rhetoric of memory in Stanisław Vincenz's novel-cycle Na wysokiej połoninie, which, along with narratology, genology and other related issues, constitutes part of Vincenz's multi-aspect mnemology. The discussion on rhetoric of memory, as the art of expression (oral and written) marked mnemically and contributing to prose of memory, centers on certain sets defining linguistic, stylistic, rhetorical and mnemotechnical means, appearing in the form of words, phrases, metaphors, idioms, and other compositional and textual ways of expression etc., which are linked semantically, etymologically, metaphorically or functionally with the fundamental lexeme, i.e. "memory". The memory category inscribed in the Vincenz work is first of all viewed here in terms of style and linguistics taking mainly into account the issues concerning memory metaphors as primary figures in rhetoric of memory. Moreover, the problems of intertextual memory are outlined therein.